1995
DOI: 10.1083/jcb.131.2.279
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional structural dissection of Drosophila polytene chromosomes.

Abstract: Abstract. We have analyzed the three-dimensional structural details of Drosophila melanogaster polytene chromosome bands and interbands using three-dimensional light microscopy and a novel method of sample preparation that does not involve flattening or stretching the chromosomes. Bands have been visualized in unfixed chromosomes stained with the DNA specific dye 4,6-Diamidino-2-phenylindole (DAPI). Interbands have been visualized using fixed chromosomes that have been immunostained with an antibody to RNA pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 63 publications
2
17
0
1
Order By: Relevance
“…Therefore, a locally defined PSF is unlikely to remove the effects of spherical aberration using a global deconvolution. However, there is evidence suggesting that high-quality deconvolution of images of thick objects can be achieved without introducing this complexity into the deconvolution algorithm [11,26]. In our lab, we have recently obtained similar images, using setups that are up to 25 μm below the cover slip [17].…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, a locally defined PSF is unlikely to remove the effects of spherical aberration using a global deconvolution. However, there is evidence suggesting that high-quality deconvolution of images of thick objects can be achieved without introducing this complexity into the deconvolution algorithm [11,26]. In our lab, we have recently obtained similar images, using setups that are up to 25 μm below the cover slip [17].…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies suggested that interchromatid cohesion is generated and maintained in the banded regions (Ananiev and Barsky 1985;Urata et al 1995). H1 is widely distributed in euchromatic arms of polytene chromosomes; however, it localizes predominantly to bands of compacted chromatin (Fig.…”
Section: The Roles Of Drosophila H1 In Sister Chromatid Adhesionmentioning
confidence: 99%
“…Prior to viewing, immunostained tissue was embedded in polyacrylamide gel using a procedure based on methods published previously (Urata et al 1995;Bass et al 1997). Briefly, the immunostained ovarioles in PBST were placed on a coverslip within an area enclosed by dried nail polish or Scotch invisible tape, and as much PBST as possible was aspirated.…”
Section: Ovary Fixation and Immunofluorescencementioning
confidence: 99%